The Role of the Hospitality Sector in Labor Absorption in Mamuju Regency - MS, A. Muh Nur Alam; Rusli; Halim, Abdul (Jurnal Economic Resource, 2024)
The hospitality sector has an important role in the economy of a region and also in the tourism industry Hotels open up jobs for many people, both directly (such as hotel staff) and indirectly (such as local suppliers). This can increase the income of residents and encourage economic growth. Hotels provide a place to stay for tourists, which is an important aspect of the tourism industry. The existence of good hospitality infrastructure, tourism can develop well, attract more tourists, and increase income from the hospitality tourism sector often triggers the development of other infrastructure, such as roads, transportation, and other public facilities, which are beneficial to the public. Grand Maleo Hotel & Convention Mamuju has a role in the absorption of manpower, either directly or indirectly providing many types of direct jobs, such as receptionists, janitors, housekeeping, chefs, waiters, building maintenance technicians, security, and management. Grand Maleo Hotel & Convention Mamuju provides a wide range of employment opportunities for a wide range of hospitality backgrounds as well as playing a role in providing opportunities for career development. The data analysis method used in this study is data analysis carried out continuously from the beginning to the end of the research, both in the field and outside the field by using techniques as proposed by Miles and Huberman, namely data reduction, data presentation and data verification. The results show that Grand Maleo Hotel & Convention Mamuju contributes to improving the quality of the workforce through training and skill development programs. Many hotels offer specialized skills training, such as customer service, foreign language proficiency, time management, and knowledge of occupational safety and security. This helps Grand Maleo Hotel & Convention Mamuju employees in improving their competence, which in turn increases the competitiveness and productivity of the workforce, in addition to helping to reduce seasonal unemployment in the area, while providing opportunities for job seekers, especially young people, to gain work experience. Hospitality has a big role in the absorption of labor.